Design and analysis of webquest materials for school mathematics - Syed Zamri, S.N.A. (2008)
WebQuest is an inquiry-oriented teaching technique that incorporates the use of information from the internet in the process of teaching and learning mathematics. The proponents and developer of WebQuest Bernie Dodge (1997, 2005) and Tom March (1998, 2000)claimed that WebQuest are designed to maximized learners' time well, emphasized on using information rather than looking for it, and can help improve students' higher order thinking through open ended questions and authentic task. Well designed WebQuest is learner centered embracing constructivist philosophy; critical and creative thinking, understanding and transformational learning, authenticity and situated learning environments; inquiry-based learning; scaffolding; differentiation, cooperative and engaged learning (Lamb & Tecleheimanot, 2005). WebQuest comprises six main elements: Introduction, Task, Process/Procedures, Resources, Evaluation and Conclusion.